(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
The Results section is a core component of the IMRaD (Introduction, Methods, Results, and Discussion) structure in scientific writing. It presents research findings objectively and systematically without interpretation or subjective commentary. This article explores the principles, structure, and writing techniques of the Results section in IMRaDbased academic writing. It examines international publishing standards, data presentation methods, use of tables and figures, statistical reporting conventions, and language features required in scholarly communication. The article also discusses common mistakes, disciplinary variations, and strategies for improving clarity and accuracy in presenting research findings. The findings show that a well-structured Results section enhances scientific transparency, improves peer-review outcomes, and strengthens research credibility. The article concludes that mastering Results writing is essential for successful publication in international academic journals indexed in Scopus and Web of Science.